Optimal factors estimation for diesel/methanol engines changing methanol injection timing and inlet air temperature. (15th December 2017) - Wu, Horng-Wen; Fan, Chen-Ming; He, Jian-Yi; Hsu, Tzu-Ting
Abstract: Methanol has been injected at the intake port with heated inlet air in a diesel engine. In the meantime, the Taguchi methodology was adopted to estimate the optimal methanol-energy-share ratio, methanol injection timing, and inlet air temperature. The injection timing and the quantity of methanol were controlled by an ECU (electronic control unit) on an electronic injector. The inlet air temperature was raised by an electric heater. The authors estimate the optimal combination of factors for larger brake thermal efficiency ( η b ), smaller smoke, NOX, HC and CO pollutant emissions for different loads. In addition, net heat release rate is obtained by the measured in-cylinder pressure data. Comparison of between the optimal combination of factors and original conventional diesel engine is made by η b, smoke, NOX, HC, CO and net heat release rate. Carrying out the confirmation tests can show that the predictions of the Taguchi methodology agree with the confirmation tests in the 95% confidence level. For the optimum combinations of factors, the maximum decrease percentage is 41.5% for smoke emission, 61.7% for NOX, 8.6% for HC emission, and 32.4% for CO emission. Highlights: We use inlet air heater and methanol injector with ECU in a diesel/methanol engine. Optimum factors are found for high combustion performance and low emissions. Methanol-energy-share ratio contributes to HC and CO more than any other factors. Inlet air temperature contributes to smoke and NOX more than any other factors. Smoke decreases up to 41.5%, NOX up to 54.7%, HC up to 8.6%, CO up to 25%.